Empowerment of Women… From Value Education to the Creation of Human Morality (Journal of the College of Education for Women, 2019)
This research on women under the title (Empowerment of women… From value education to the creation of human morality), includes a disclosure of the reasons that prevented women from performing their human role in the development of human societies and treatments that can provide to solve this big problem in the life These communities, especially the Eastern societies and the religious ones, believe that the woman has not received the care and care to raise her human values ​​in order to contribute to the required social contribution, for historical, economic, moral, religious, social and cultural reasons. And by shedding light on specific definitions of the most important rules on which the research relied on in order to create a sound answer to the essence of the problem and to the basic question that the research is trying to address. These rules include conceptual reading of values, research in humanity as moral, And detail in the Empowerment Project as the starting point for the work from the moral inside to the practical outside. The research also discussed a number of topics related to the substance of the problem, including talking about women's freedom and condemning them as total values ​​required. On the one hand, freedom is an affirmation of women's self, and religion is an affirmation of the surrounding issue affecting women.